A MANAGED APPROACH OF INTERACTION BETWEEN AGILE SCRUM AND SOFTWARE CONFIGURATION MANAGEMENT SYSTEM - Parvez, ABU WAHID MD. MASUD (Jurnal Sistem Komputer, 2012)
In current age the agile software development is one of the most popular software development methodology but due the mismanagement and lack of efficient handling of agile scrum and software configuration management system our software industry is facing a high rate of failed product, keeping this as my motivation, I have designed a efficient checklist which will help the industry to organized the interaction between agile scrum process and software configuration management system in a efficient and managed way and definitely that will increase the successful project in the software industry.